"Going the Extra Mile": Satisfaction and Alliance Findings from an Evaluation of Videoconferencing Telepsychology in Rural Western Australia. (August 2015) - Richardson, Lisa; Reid, Corinne; Dziurawiec, Suzanne
<x xml:space="preserve">Abstract</x> Objective Technology is changing how we behave, communicate, and process information, and this has significant implications for mental health care. Telepsychology has appeal as a solution to obstacles of distance and access in rural and regional areas; however, few services appear to provide telepsychology as a routine service component for psychotherapeutic exchanges. The primary research goal of a multi‐year PhD project was to explore and explain the disconnect between research and practice in telepsychology, and to investigate, among other things, how telepsychology changes the clinician's usual practice or the client's behaviour. Methods Eight adult participants were seen for 68 hours of direct videoconferencing telepsychology over 11 months, and 53 separate points of data for each client that included the perspectives of both the client and therapist were collected. Clients completed technical, process, and therapy‐based satisfaction surveys after each session, in addition to standardised clinical symptom rating. Results This manuscript will summarise some of the project's research findings in relation to specific practice techniques, with a particular focus on therapeutic alliance and satisfaction. Conclusions In possible contrast to the opinions of those less familiar with telepsychology, we conclude that if telepsychology is not treated apologetically it can achieve therapeutic results, albeit via a different route, favourably comparable to those achieved in face‐to‐face encounters.